Motivation for skill transfer: Mediating role of e-learner's satisfaction - Muhammad Zia-ur-Rehman; Irram Shahzadi (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
Transfer motivation is of huge importance in training and effective management of knowledge. This study aims to explore the structural association of operative factors (internal value, learning usefulness, learning environment, learner satisfaction) and motivation of e-learner, for effective skill transfer. Online survey was conducted to collect data from 200 students of Virtual University, who were enrolled in two subjects: Knowledge Management and Organizational Behavior. Data was analyzed using SPSS and AMOS. Results of Structural Equation Modeling (SEM) found that the structural association among e-learners' internal value, learning usefulness, learning environment, satisfaction, and motivation for skill transfer is significantly positive. Nonetheless, the study found a weak association among learning environment, and motivation for skill transfer. Some propositions were made to augment e-learners' learning outcomes e.g. enhance sample size, take data from students of other courses as well, some other variables (social belongingness, achievements of e-learner) must be taken into account. This study endows with an integrated view of e-learner's effective factors of motivation for skill transfer in e-learning environment.
Keywords: 330; motivation for skill transfer; e-learner's satisfaction; learning usefulness; learning environment